2012
DOI: 10.5423/ppj.2012.28.2.172
|View full text |Cite
|
Sign up to set email alerts
|

A Forecast Model for the First Occurrence of Phytophthora Blight on Chili Pepper after Overwintering

Abstract: An infection risk model for Phytophthora blight on chili pepper was developed to estimate the first date of disease occurrence in the field. The model consisted of three parts including estimation of zoosporangium formation, soil water content, and amount of active inoculum in soil. Daily weather data on air temperature, relative humidity and rainfall, and the soil texture data of local areas were used to estimate infection risk level that was quantified as the accumulated amount of active inoculum during the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…The pathogen causes not only root and crown rot of pepper, but also aerial blight of the leaves, fruit, and stems. The survivals of sporangia, zoospores, and hyphae of P. capsici are short lived in fields, but its thick-walled oospores are durable and play a key role in the infectious life cycle, surviving under unfavorable conditions for long periods of time and serving as a dispersal propagule when established in the soil (McDonald and Linde, 2002;Do et al, 2012). Removing viable oospores from the field is therefore of great importance in the control of Phytophthora blight.…”
Section: Introductionmentioning
confidence: 99%
“…The pathogen causes not only root and crown rot of pepper, but also aerial blight of the leaves, fruit, and stems. The survivals of sporangia, zoospores, and hyphae of P. capsici are short lived in fields, but its thick-walled oospores are durable and play a key role in the infectious life cycle, surviving under unfavorable conditions for long periods of time and serving as a dispersal propagule when established in the soil (McDonald and Linde, 2002;Do et al, 2012). Removing viable oospores from the field is therefore of great importance in the control of Phytophthora blight.…”
Section: Introductionmentioning
confidence: 99%
“…weather data to identify conditions for infection Magarey et al, 2005) or to simulate one or more processes in disease cycle (De Wolf and Isard, 2007;Do et al, 2012;González-Domínguez et al, 2014;Olatinwo and Hoogenboom, 2014;Park et al, 1997). By using observed weather data from automated weather stations (AWS) at near real-time basis, the models are able to determine if weather conditions favorable for pathogen infection have occurred in the immediate past period.…”
mentioning
confidence: 99%
“…Daily precipitation and soil water content of the experimental field which were estimated by sub-models of PBcast(Do et al, 2012) based on observed ambient temperature, precipitation and soil texture data in 2012 and 2013. Soil texture data were obtained from the National Institute of Agricultural Sciences, Rural Development Administration of Korea.…”
mentioning
confidence: 99%
“…Daily mean ambient temperature and soil temperature monitored by an automated weather station installed at the chili pepper field of Chungcheongbuk-do Agricultural Research and Extension Services during the growing seasons of 2012 and 2013. Daily mean soil temperature were estimated were estimated by a sub-model of PBcast(Do et al, 2012) based on observed ambient temperature.…”
mentioning
confidence: 99%